Patterns and Correlates of Intergenerational Non-Time Transfers Evidence from CHARLS - Lei, Xiaoyan (The World Bank, 2012)
Using the China Health and Retirement Longitudinal Study 2008 pilot, this paper analyzes the patterns and correlates of intergenerational transfers between elderly parents and adult children in Zhejiang and Gansu Provinces. The pilot is a unique data source from China that provides information on the direction as well as amount of transfers between parents and each of their children, and clearly distinguishes transfers between parents and children from those among other relatives or friends. The paper shows that transfers flow predominantly from children to elderly parents, with transfers from children playing an important role in elderly support. Taking advantage of the rich information available in this survey, the authors find strong evidence that transfers are significantly affected by the financial capabilities of individual children. Educated and married children have a higher tendency to provide transfers to their parents; and oldest sons are less likely to provide transfers than their younger brothers. With future continued rapid economic growth in China, the income disadvantage of the elderly will persist and upward generational transfers will likely remain the most common form of private transfers. In the absence of some other source of elderly support (such as a public pension or own savings), the dwindling number of children implies that the financial burden associated with supporting the elderly is likely to increase